PENGARUH BEBAN KERJA, KOMPETENSI, DAN SUPERVISI AUDIT TERHADAP KUALITAS AUDIT - ,Susilatri, Anisha Octa Alivia ,Andreas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The purpose of this research was to analyze the effect workload, competence, and audit supervision on audit quality at Public Accounting Firm in Pekanbaru and Medan, which consist of senior auditors, junior auditors, partners, and supervisor. The research used a quantitative methode by distributing questionnaires as the primary data that is gained from respondent. Questionnaires were distibuted by 84 questionnaires, of 84 questionnaires were distributed, which can be processed only 63 questionnaires. The result of the research showed the workload, competence, and audit supervision had significant effect on audit quality. Keywords: workload, competence, audit supervision, and audit quality